Pembangunan tarian tradisional Zapin di Sarawak dalam memartabatkan seni tari Melayu Sarawak - Lawrence, Dino (University Malaysia Sarawak, (UNIMAS), 2007)
The purpose of research is to explore the development of Zapin Sarawak traditional dance especially Zapin Sebat and Zapin Sindang as one of Sarawak traditional Malay dance. It relates with the effort by cultural oganizations in order to introduce, nurture, preserve and to develop Zapin Sarawak. Thus, with this effort it could raise up Zapin Sarawak as one of the original heritage of Sarawak Malay dance.